Venture capital as a way to develop an innovative model of the Russian economy - L. K. Bzegezheva (Вестник университета, 2023)
The article studies the way to develop an innovative model of the Russian economy by organizing venture capital investment. The purpose of the study is to analyze structural changes in the venture investment mechanism in Russia that have been occurring against the background of Russia’s special operation in Ukraine since February 24, 2022. The objectives of the study include identifying the role and significance of venture capital in the Russian economy transformations. The author used the methods of statistical, financial, dialectical and logical analysis. The system approach is fundamental, as it allowed to identify all the essential characteristics of structural changes in venture investment mechanism in the changed economic environment. The time period of the study is 2017–2022. The study analyzes the data from international organizations, analytical centers, mass media, and official sources. A review of the literature has been made and various approaches of scientific research considered. The main functions of venture capital have been highlighted and sources of its formation by directions given, and differences in the regulatory framework governing the Russian and other countries’ venture capital industry identified.